2009
DOI: 10.1007/s10640-009-9321-5
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Benefits of Neighbourhood Park Amenities: Application and Comparison of Spatial Hedonic Approaches

Abstract: Hedonic approach, Kriging, Spatial autocorrelation, Spatial regression models, Urban parks,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 29 publications
(31 reference statements)
0
33
0
2
Order By: Relevance
“…For the average size of 121 m 2 in the sample, an increase in one unit would raise the price by $4410. Other authors have included in their models variables that described the type of property (Moracho 2003; Sunak and Madlener 2012), although some other authors have preferred to analyse only a specific type of property to maintain consistency in the levels of variability across the sample (Tyrv€ ainen and Miettinen 2000; Hoshino and Kuriyama 2010). In this study, the marginal implicit price for a detached house was found to be $271,420, and that for a duplex or penthouse was $133,880.…”
Section: Hedonic Pricing Modelling Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the average size of 121 m 2 in the sample, an increase in one unit would raise the price by $4410. Other authors have included in their models variables that described the type of property (Moracho 2003; Sunak and Madlener 2012), although some other authors have preferred to analyse only a specific type of property to maintain consistency in the levels of variability across the sample (Tyrv€ ainen and Miettinen 2000; Hoshino and Kuriyama 2010). In this study, the marginal implicit price for a detached house was found to be $271,420, and that for a duplex or penthouse was $133,880.…”
Section: Hedonic Pricing Modelling Resultsmentioning
confidence: 99%
“…In this study, the marginal implicit price for a detached house was found to be $271,420, and that for a duplex or penthouse was $133,880. The age of the building was not included as an independent variable, as it has been in some other studies (Tyrv€ ainen and Miettinen 2000;Tapsuwan, Ingram, and Brennan 2007;Hoshino and Kuriyama 2010). However, in this study, two dummy variables that describe the state of the building ('property built in 2003 or after' and 'property renovated in 2003 or after') were used.…”
Section: Hedonic Pricing Modelling Resultsmentioning
confidence: 99%
“…Equipped with six schools and six parks, the TUSD is a university special zone featuring a low building coverage ratio, high greenness coverage, underground cables and telecommunications equipment, and an environment tuned for living. Previous studies have found that factors such as school quality (Ries and Somerville, 2010) and park size (Song and Knaap, 2004;Hoshino and Kuriyama, 2010) have significant influences on housing prices. In the case of implementing revitalization projects to rundown areas (to the south of the TUSD is Old Sanxia and to the north is Old Shulin), these projects fail inevitably because of the lack of public participation and explicit policy support (Leinberger, 2005).…”
Section: Hypothesismentioning
confidence: 99%
“…A growing number of studies in the urban and real estate economics literature has examined the pricing effects of urban amenities (e.g., Gibbons et al 2014;Ahlfeldt and Maennig 2010;Hoshino and Kuriyama 2009;Anderson and West 2006;Dehring and Dunse 2006). In these studies, the implicit values of urban amenities are revealed from the observed housing market using the hedonic pricing model developed by Rosen (1974).…”
Section: Literature Reviewmentioning
confidence: 99%